2011
DOI: 10.1016/j.surg.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Efferent vagal nerve stimulation attenuates acute lung injury following burn: The importance of the gut-lung axis

Abstract: Background The purpose of this study was to assess acute lung injury when protection to the gut mucosal barrier offered by vagus nerve stimulation is eliminated by an abdominal vagotomy. Methods Male balb/c mice were subjected to 30% total body surface area steam burn with and without electrical stimulation to the right cervical vagus nerve. A cohort of animals were subjected to abdominal vagotomy. Lung histology, myeloperoxidase and ICAM-1 immune staining, myeloperoxidase enzymatic assay, and tissue KC leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…Breakdown of the gut barrier is associated with increases in systemic inflammation, distant organ injury, and death [4,6,7,14,20]. Studies have shown that modulation of intestinal epithelial tight junction proteins, through VNS, may be a potential strategy for attenuating gut barrier failure after injury [5,6,[13][14][15]. In this study, we explore the signaling pathway by which VNS maintains gut barrier integrity after injury, specifically focusing on the role of EGCs.…”
Section: Discussionmentioning
confidence: 99%
“…Breakdown of the gut barrier is associated with increases in systemic inflammation, distant organ injury, and death [4,6,7,14,20]. Studies have shown that modulation of intestinal epithelial tight junction proteins, through VNS, may be a potential strategy for attenuating gut barrier failure after injury [5,6,[13][14][15]. In this study, we explore the signaling pathway by which VNS maintains gut barrier integrity after injury, specifically focusing on the role of EGCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, at present, there is still a lack of effective drugs or interventions to protect the gut epithelial barrier. Recent studies showed that electrical stimulation of the vagus nerve could protect intestinal barrier and alleviate inflammatory injury in intestine and remote organs of animals following burn injury by activation of the cholinergic anti-inflammatory pathway [58]. However, it is still difficult to apply electrical stimulation to the vagus nerve in clinical practice due to complicated manipulation and untoward side effects, including serious tissue injury.…”
Section: Introductionmentioning
confidence: 99%
“…9 In this schema, when the neuroenteric axis is activated by VNS in a burn model, secondary acute lung injury is prevented. However, if abdominal vagotomy is performed, protective effects of VNS are eliminated and secondary acute lung injury occurs via the gut-lung axis.…”
mentioning
confidence: 99%
“…However, if abdominal vagotomy is performed, protective effects of VNS are eliminated and secondary acute lung injury occurs via the gut-lung axis. 9 …”
mentioning
confidence: 99%